H2O2 Signature and Innate Antioxidative Profile Make the Difference Between Sensitivity and Tolerance to Salt in Rice Cells - Formentin, Elide; Sudiro, Cristina; Ronci, Maria Beatrice; Locato, Vittoria; Barizza, Elisabetta; Stevanato, Piergiorgio; Ijaz, Bushra; Zottini, Michela; De Gara, Laura; Lo Schiavo, Fiorella (Frontiers in Plant Science, 2018)
Salt tolerance is a complex trait that varies between and within species. H2O2 profiles as well as antioxidative systems have been investigated in the cultured cells of rice obtained from Italian rice varieties with different salt tolerance. Salt stress highlighted differences in extracellular and intracellular H2O2 profiles in the two cell cultures. The tolerant variety had innate reactive oxygen species (ROS) scavenging systems that enabled ROS, in particular H2O2, to act as a signal molecule rather than a damaging one. Different intracellular H2O2 profiles were also observed: in tolerant cells, an early and narrow peak was detected at 5 min; while in sensitive cells, a large peak was associated with cell death. Likewise, the transcription factor salt-responsive ethylene responsive factor 1 (TF SERF1), which is known for being regulated by H2O2, showed a different expression profile in the two cell lines. Notably, similar H2O2 profiles and cell fates were also obtained when exogenous H2O2 was produced by glucose / glucose oxidase (GOX) treatment. Under salt stress, the tolerant variety also exhibited rapid upregulation of K+ transporter genes in order to deal with K+/Na+ impairment. This upregulation was not detected in the presence of oxidative stress alone. The importance of the innate antioxidative profile was confirmed by the protective effect of experimentally increased glutathione in salt-treated sensitive cells. Overall, these results underline the importance of specific H2O2 signatures and innate antioxidative systems in modulating ionic and redox homeostasis for salt stress tolerance.